Kepemimpinan dalam Pendidikan Islam - Fahmi Khumaini; Rz. Ricky Satria Wiranata (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2019)
Leadership comes together with the existence of human civilization that is since the time of the prophets and human ancestors. Since then there has been cooperation between people, and there is an element of leadership. Leadership is a social fact that can not be avoided to regulate relationships between individuals who are members of a community Leadership is a matter of relations between leaders and those who are led. The leadership appears and develops as a result of automatic interaction between leaders and individuals who are led. The ideal nature of leaders in Islam is extensive knowledge, there is a spirit to encourage goodness, noble character, istiqomah, patience, fairness, honesty, discipline, responsible spirit and have the spirit to develop, leaders who inspire, instill the spirit of mutual cooperation to realize the vision and joint mission. The most important point of the function and purpose of leadership in Islamic education is to be able to grow wise new leaders as regulated in Islamic teachings